Digitalization and Transparency in Efforts to Prevent and Eradicate Corruption - Timomor, Adensi; Pangalila, Theodorus (Technium Social Sciences Journal, 2026)
This study aims to examine and analyze whether digitalization systems can create transparency and prevent corrupt behavior, particularly within local government institutions at the regency and municipal levels in North Sulawesi. It also seeks to analyze the factors that hinder the transition of government management from a reactive to a proactive model, as well as to examine the role of the government in facilitating this transition toward digitalization as part of efforts to prevent corruption. The method employed in this study is normative legal research combined with field research, including surveys and interviews conducted at regency and municipal government offices that serve as the research objects. The approaches used in this study include the statute approach, analytical approach, and conceptual approach. Through these approaches, the study first examines how laws have been applied in efforts to prevent corrupt behavior, and subsequently evaluates the appropriateness of the concepts of corruption prevention and eradication. Furthermore, it analyzes whether the aspect of transparency is reflected in policies aimed at preventing and combating corruption. The findings of this study indicate that the governmental management systems in several regencies and municipalities in North Sulawesi have adopted digital technology, and that the digitalization process has had a positive and significant impact. It has contributed to the creation of transparency and has exerted a psychological effect across all levels of government management, from village/urban village administration to regional government institutions. With digital-based management systems, civil servants (ASN) are able to access data internally, thereby making digitalization an effective and transparent monitoring instrument that can reduce the intention to engage in corrupt behavior. However, human resources remain one of the main factors hindering the acceleration of the transition from reactive to proactive digital-based management.